FRI0062 Evaluation of a multi-biomarker disease activity (vectra ™ da algorithm) in early rheumatoid arthritis and unclassified arthritis patients. (23rd January 2014) - Maijer, K. I.; de Hair, M. J. H.; Li, W.; Defranoux, N. A.; Sasso, E. H.; Gerlag, D. M.; Tak, P. P.
Abstract : Background: Accurate and frequent assessment of rheumatoid arthritis (RA) is critical for optimal treatment planning and would benefit from the availability of an objective, sensitive and robust way to measure disease activity. The multi-biomarker disease activity (MBDA) test is a novel validated assay that measures the serum concentration of 12 biomarkers and combines them in a score that measures disease activity in patients with RA. Objectives: To evaluate the MBDA score as a measurement of disease activity in early RA and unclassified arthritis (UA) patients. Methods: 126 patients who were enrolled in the prospective early arthritis cohort of the Academic Medical Center in Amsterdam and had arthritis duration <1 year and were naïve to disease modifying anti-rheumatic drugs were selected for this study. At baseline patients either fulfilled the 2010 ACR/EULAR criteria for RA (n=81) or had unclassified arthritis (UA) and didn't fulfill classification criteria for established rheumatic diseases (n=45). Patients were followed for 2 years and those with UA were categorized as having either converted to RA (UA-RA) or remained unclassified (UA-UA). Serum samples were collected at baseline and concentrations of VCAM-1, EGF, VEGF-A, IL-6, TNF-RI, YKL-40, MMP-1, MMP-3, leptin, resistin, SAA, CRP were measured using a multiplex immune assay. The MBDA score (1-100) was calculated using the validated Vectra™ DA algorithm [1 ]. To compare disease activity parameters between RA and UA patients Mann-Whitney U test was performed. Correlations between the MBDA score and other disease activity parameters (ESR, CRP, DAS28-ESR, 66 swollen joint count (SJC66)) were examined using Spearman's rank correlation coefficient. Results: At baseline, median (IQR) MBDA scores were significantly greater in early RA patients (46 (34-62)) than in UA patients (35 (18-46)) (p=0.001); as were the median (IQR) values of baseline ESR: 25 (11-37) vs. 12 (5-26); CRP: 8.0 (3.7-28.7) vs. 3.0 mg/l (1.8-13.9); DAS28-ESR: 5.1 (4.3-6.1) vs. 3.3 (2.7-4.0); and SJC66: 7 (4-12) vs. 2 (1-4), with all p-values <0.001. In early RA patients, the median baseline MBDA score correlated with baseline ESR (r=0.59), CRP (r=0.83), DAS28-ESR (r=0.57) and SJC66 (r=0.42) with all p-values <0.001. Correlations between these parameters were also observed in the UA patients. Furthermore, in early RA patients with levels of CRP <5mg/L (n=59), the MBDA score correlated with ESR, DAS28-ESR and SJC66. Conclusions: This was the first single-center study to assess both early RA and UA patients with the MBDA score. We showed that the score correlated with clinical disease activity measurements independently of the early RA or UA diagnosis. In addition, we showed that the MBDA score may be used to assess disease activity in early arthritis patients who had CRP levels <5mg/ L. References: Curtis JR, et al., Validation of a novel multi-biomarker test to assess rheumatoid arthritis disease activity. Arthritis Care & Research 2012 Dec; 64(12):1794 Disclosure of Interest: K. Maijer: None Declared, M. de Hair: None Declared, W. Li Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, N. Defranoux Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, E. Sasso Shareholder of: Crescendo Bioscience, Employee of: Crescendo Bioscience, D. Gerlag: None Declared, P. P. Tak: None Declared